Innovation and knowledge management - Anderson, Neil, 1961-; Costa, Ana Cristina; Sage eBooks (Los Angeles, [Calif.] : SAGE, 2010)
Innovation and knowledge management has gained considerable importance over the last 40 years, both as an area of academic research and as an area of professional practice. Each volume of this set covers a key area of innovation and knowledge management, reflecting both historical roots and cutting-edge scholarship.
v. 1. Individual creativity and innovation -- v. 2. |t Work group and team innovation -- v. 3. Organizational innovation -- v. 4. Knowledge management.
Specialized.
Description based on print version record.
Includes bibliographical references.
Keywords: Organizational change -- Management; Technological innovations; Organizational learning; Knowledge management; Information technology -- Management; Electronic books